Pengaruh Penambahan Zat Kapur dan Lama Perendaman Terhadap Kadar Sianida pada Singkong (Manihot Esculanta Crantz) - Sulfiani Ani Hasan; Nuramaniyah Taufiq (Jurnal Sehat Mandiri, 2022)
Cassava (Manihot esculenta Crantz) or also known as cassava has a high carbohydrate content and has become the third staple food source after maize and rice. Cassava also contains linamarin and lotaustralin poisons which belong to the cyanogenic glycoside group. Cyanogenetic glycosides are compounds found in plant foodstuffs and are potentially very toxic because they decompose and release hydrogen cyanide. This study aims to determine the cyanide acid content in cassava before being soaked in lime solution and to determine the cyanide acid content in cassava after soaking in lime solution with concentrations of 0.25%, 0.50%, 0.75%, 1% and 2% for 2 hours, 4 hours, and 6 hours. Using argentometry method. Soaking with lime concentrations of 0.25%, 0.50%, 0.75%, 1% and 2% does not affect the cyanide acid levels, which affects the cyanide levels, namely the long soaking time which is 2 hours can reduce the cyanide acid levels. up to 50%, soaking time of 4 hours reduced 62.5% and soaking time of 6 hours reduced up to 75% the level of cyanide acid contained in cassava. Based on the research, it can be concluded that the soaking time greatly affects the decrease in cyanide levels found in cassava. Suggestions should try measurements using instrumentation methods.